The Impact of COVID-19 Crises on the Diet Quality, Physical Activity, and Sedentary Lifestyle Among Saudi’s Adults: COVID-19 Crises on the Diet Quality, Physical Activity, and Sedentary Lifestyle - Jalloun, Rola; Alahmadi, Mohammed (Progress in Nutrition, 2022)
The COVID-19 pandemic has affected day-to-day life and is changing how we eat and even how we exercise, as many individuals have developed a passive sedentary lifestyle. The aim of the study is to assess the impact of the COVID-19 crisis on dietary quality, physical activity, and sedentary behavior among Saudi adults. A descriptive cross-sectional study was conducted among 738 adults in the KSA. A modified Dietary Quality Score (DQS) The International Physical Activity Questionnaire (IPAQ) and the Sedentary Behavior Questionnaire (SBQ) were used for the purpose of the study. The results showed that the overall proportion of participants with average dietary habits was 76%, and 16% of the participants were identified as having unhealthy dietary habits. The total average length of PA in minutes/week was 2079.08 ±2454.14, and the highest average was for vigorous PA (1372.47 ±1665.62 minutes/week). The SBQ indicated that the total length of SB was 552.36 ± 253.11 minutes/week. Meanwhile, on average, participants spent the most time using the internet (213.75 ± 153.81 minutes/day) and the least time talking on the phone (46.53 ± 56.80 minutes/day). Overall, 34.7% of the sample spent ≥ 7 hours/day sitting; this pattern was observed more in females than in males. Finally, 65.3% of the sample spent < 7 hours/day sitting; this pattern appeared significantly more often in males than in females. The COVID-19 crisis has rapidly affected people’s daily lives, including dietary quality, physical activity and sedentary behavior. This pandemic has caused significant effects on the lifestyle, quality of life and well-being of individuals and societies, and it may continue to affect them in the future.